Serine Supports IL-1β Production in Macrophages Through mTOR Signaling - Chen, Siyuan; Xia, Yaoyao; He, Fang; Fu, Jian; Xin, Zhongquan; Deng, Baichuan; He, Liuqin; Zhou, Xihong; Ren, Wenkai (Frontiers in Immunology, 2020)
Intracellular metabolic programs tightly regulate the function of macrophages, and previous studies have shown that serine mainly shapes the macrophage function through one-carbon metabolism. However, it is unknown whether serine modulates the macrophage function through mechanism independent on one-carbon metabolism. Here, we find that serine deprivation lowers the production of interleukin (IL)-1β and activation of cellular inflammasome, as well as reprograms the transcriptomic and metabolic profile in M1 macrophages. Interestingly, supplementation of formate, glycine, dNTPs and glucose cannot rescue the production of IL-1β from serine-deprived macrophages. Mechanistically, serine deprivation inhibits the macrophage IL-1β production through inhibition of mechanistic target of rapamycin (mTOR) signaling. Notably, the macrophages from mice feeding serine free diet have lower production of IL-1β, and these mice also have lower inflammation after LPS challenge. Collectively, our data highlight a new regulatory mechanism for serine to modulate the macrophage function.